ANALYSIS OF THE APPLICATION OF THE TALAQQI METHOD IN IMPROVING SHORT HADITH MEMORIZATION IN EARLY CHILDHOOD - Wahyuni, Akhtim; Indriani, Lia; Rahmawati, Erlinda Nur (PT. Antis International Publisher, 2025)
Objective: This research aims to analyze the effectiveness of applying the Talaqqi method in improving hadith memorization in early childhood and determine the supporting and inhibiting factors in its application. Method: The Talaqqi method is a method that can be used to memorize hadith by imitating the teacher's reading. Results: This research shows that the application of the Talaqqi method is effective in improving the ability to memorize hadiths in young children. The results of this research show that the Talaqqi method has advantages such as improving the quality of memorization and making it easier for children to memorize hadiths. Novelty: However, in this research, it was also found that teachers faced difficulties in implementing the Talaqqi method, namely the lack of parental attention to providing reinforcement of hadiths that had been memorized at school.